Coronary atherosclerosis in medico-legal autopsy cases - Prasad, VN; Jha, A; Adhikari, RC; Sayami, G; Shrestha, PK; Shrestha, HG (Journal of Pathology of Nepal, 2014)
Background: Coronary atherosclerosis is the major cause of death worldwide. Lifestyle and habits are the major contributory factor in the development of coronary atherosclerosis. Materials and Methods: This is an autopsy-based study in which 45 autopsy cases were randomly selected for study. Proximal one third of all three epicardial coronary arteries (LAD, LCX and RCA) were dissected out for study and serial sections were made and stained with H&E method and under the light microscope. Atherosclerosis was graded according to American heart association classification. The risk factors (cigarette smoking, hypertension, diabetes, alcohol consumption, age, sex) were also correlated with the grade of atherosclerosis. Results: Seventy-Eight percent of American Heart Association classification grade V lesions were seen in > 70 yrs of age. Almost all cases of > 70 yrs of age had American Heart Association classification grade > IV lesions. Out of all grade IV lesions, 88.9% was seen in male while only 11.1% in female. Similarly out of all grade V lesions, 77.8% was seen in male while 22.2% in female. LAD showed maximum involvement by higher grade lesion, followed by LCX and RCA. American Heart Association classification grade > IV in LAD, LCX and RCA was seen in 25(55.6%), 5(11.1%), and 3(6.7%) cases respectively. Conclusion: Higher grade lesion occurs in advancing age. Various cardiovascular risk factors were significantly associated with higher grade of lesions. The multiple risk factors had a synergistic effect on the progression of coronary atherosclerosis. DOI: http://dx.doi.org/10.3126/jpn.v4i8.11492 Journal of Pathology of Nepal; Vol.4,No8(2014) 607-611